1994
DOI: 10.1039/ft9949002211
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the diamminecopper(I) ion in solution. An X-ray absorption spectroscopic study

Abstract: X-Ray absorption spectroscopy (XAS) using synchrotron radiation has been used to probe the structure of copper(1) species in an aqueous ammonia solution that contains hydrazine to prevent any oxidation to copper(n) species. Combining a characteristic copper(1) pre-edge feature with the extended X-ray absorption fine structure (EXAFS) of the XAS enabled the stereochemistry and bond distances to be extracted for the predominant species, which is shown to be the diamminecopper(~) ion. The structure is linear with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 4 publications
3
51
0
Order By: Relevance
“…The standard text-book description for Cu(I) has a coordination number of four, 103 although a concrete experimental characterization is complicated by the instability of Cu(I) toward disproportionation. 104 Indeed, in the gas phase, IR studies of Cu(normalH2O)n+ clusters 105,106 pointed to a linear dihydrate structure similar to Cu + diammine complex; 107 mass spectrometry study on water-Cu binding 108 also found that the binding energy of the third water and after dropped by a factor of two compared to the first two binding energies. The two-coordination configuration was supported by several theoretical calculations in the gas phase 96,97 and in CPMD/BOMD simulations for a solvated Cu(I).…”
Section: Resultsmentioning
confidence: 99%
“…The standard text-book description for Cu(I) has a coordination number of four, 103 although a concrete experimental characterization is complicated by the instability of Cu(I) toward disproportionation. 104 Indeed, in the gas phase, IR studies of Cu(normalH2O)n+ clusters 105,106 pointed to a linear dihydrate structure similar to Cu + diammine complex; 107 mass spectrometry study on water-Cu binding 108 also found that the binding energy of the third water and after dropped by a factor of two compared to the first two binding energies. The two-coordination configuration was supported by several theoretical calculations in the gas phase 96,97 and in CPMD/BOMD simulations for a solvated Cu(I).…”
Section: Resultsmentioning
confidence: 99%
“…It has to be stressed that the splitting of the main resonance in peaks B and C is a common feature of several Cu͑II͒ compounds. 23,25,26,[29][30][31][32]34 Then the following tests have been performed to improve the calculation: ͑i͒ more realistic self-consistency field ͑SCF͒ potentials and ͑ii͒ the incorporation of many-body processes to compute the absorption spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…1, are in agreement with previously published data. [29][30][31][32] Both FEFF8 9 and CONTINUUM 4 codes were used to calculate the Cu K-edge XANES spectra. No significant differences were found for the standard single-channel MS computations obtained by using the two different codes.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…This, together with the energies, indicates that 2p 6s(Hg) and 2p ligand orbitals are possible assignments 10,11 . In the case of copper(I) compounds at the K-edge, the intensity of the pre-edge peak is connected to the 1s 4p transitions often observed for transition metal compounds 19,20 .…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%